The association between smartphone use and myopia progression in children: a prospective cohort study - Li, Jing (BMC pediatrics, 2025)
The increasing myopia of children has sparked speculations on whether the use of smartphones can accelerate this rate. This study aims to identify possible predictors for myopic progression in children with smartphones over a period of two years. This prospective cohort study recruited 523 children aged 6 to 14 years. A comprehensive eye examination was performed at baseline and at 6, 12, and 24 months, which included spherical equivalent refractive error (with cycloplegia) and axial length. Smartphones usage patterns were traced using mobile usage monitoring app. Outdoor activities, sleep duration, and parental history of myopia were documented with structured questionnaires. Data on myopic progression associated with smartphone use are presented with multivariate regression analyses. It demonstrated that daily usage of smartphones was positively associated with the progression of myopia (5.1 ± 1.2 vs. 3.4 ± 1.0 h, p < 0.001). Increased time of outdoor activity (1.2 ± 0.6 vs. 2.1 ± 0.8 h/day, p < 0.001) and longer distances of screens (25.8 ± 5.4 vs. 31.4 ± 6.2 cm, p < 0.001) were inversely related to myopic progression. Of importance is that children whose parents experienced myopia exhibited higher progression rates compared to those who did not (65.5% vs. 44.4%, p < 0.001). This study indicated that daily duration of smartphones use, time of outdoor activity, distance of screen, and parental myopia are predictors of childhood myopic progression.